Diagnosa Penyakit Hepatitis Menggunakan Metode Sorensen Cooficient - Ilham Rizky Riyanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
In a computer technology that can help people solve problems that are widely applied in the world of medicine is an expert system. a system that is adopted from human insight into computers, thus enabling problems to be solved by computers, as developed by an expert. In this study, the Expert System can diagnose hepatitis. The system can diagnose hepatitis, which is made using the PHP programming language and MySQL database using the Sorensen Cooficient method. With input in the form of symptoms and blood tests, then the results are possible diseases suffered by the patient and an explanation of the disease and treatment solutions. So that this expert system is able to diagnose hepatitis. This study uses the Sorensen Cooficient method which can be implemented into an expert system with complex or acute hepatitis, or simple hepatitis.